EFICÁCIA CLÍNICA DO CLAREAMENTO EM CONSULTÓRIO USANDO DUAS CONCENTRAÇÕES DE PERÓXIDO DE HIDROGÊNIO COM E SEM ATIVAÇÃO - Serrano, Alexandra Patricia Mena (2013)
The objective of this study was to compare the bleaching efficacy and tooth sensitivity (TS) of two hydrogen peroxide (HP) concentrations (20 and 35%) used for in-office bleaching associated or not with a LED/laser light activation. Seventy-seven patients with right upper canine darker than A3 were selected to participate in this single-blind randomized trial. The participants were distributed in four groups: bleaching with 20% HP alone; 20% HP + LED/laser; 35% HP alone [35%]; 35% HP + LED/laser. The buccal surfaces of the anterior teeth were bleached, in two sessions, using a 35% or 20% HP gel with one week interval. At each session, three applications of 15 min were used. For the light activated groups, the LED/laser energy (Whitening Laser Light Plus, DMC) was employed according to the manufacturer’s instructions. The color change was evaluated by using the Vitapan Classical Shade Guide and the VITA Easyshade Spectrophotometer (Vita Zahnfabrik) 1 week and 1 month post bleaching. Participants recorded TS with a five-point verbal and VAS scales, and identified the sensitive tooth. Color change was analyzed by ANOVA and Tukey’s tests (α = 0.05). The absolute risk of TS and TS intensity evaluated by Fisher’s exact test and Kruskall Wallis test, respectively (α = 0.05). All groups achieved the same level of whitening at both evaluation periods, except for the 20% HP group, which showed the lowest amount of whitening as detected by the subjective evaluation. The use of light did not increase absolute risk of TS and TS intensity during and after bleaching for both scales. The premolars were the least sensitive. It can be concluded that the use of LED/laser light activation was able to increase the amount of whitening produced with the 20% HP without increasing TS, but this association was not useful for the 35% HP gel.